ANALISIS PENYUSUTAN ARSIP REKAM MEDIS DALAM RANGKA PENYELAMATAN ARSIP DI RUMAH SAKIT SETIO HUSODO KISARAN - IRAWATI, LENNI (LP2MTBM MAKARIOZ, 2022)
Hospital, what is meant by hospital is a health service institution that provides comprehensive individual health services that provide inpatient, outpatient and emergency services. A hospital is a place that provides short-term and long-term medical services which include observation, diagnostic, therapeutic and rehabilitation activities for all people suffering from illness or injury and giving birth. The aim of this research is to analyze the depreciation activities of medical record archives at Setio Husodo Kisaran Hospital. This research uses a qualitative research design with a case study approach. The data collection techniques used were observation, interviews and literature study. Data analysis in this research is data reduction, data presentation, and drawing conclusions. The results of this research explain that the House Setio Husodo Kisaran Hospital last carried out depreciation of medical record archives in 2008. Currently, depreciation is carried out by moving inactive medical record archives after a storage period of 5 (five) years for patients seeking treatment. Limited human resources and a lack of understanding by officers about the Archive Retention Schedule (JRA) are the main obstacles to the depreciation of medical record archives.